Human dignity and fundamental rights in South Africa and Ireland - Anne Hughes (Pretoria University Law Press (PULP), 2014)
Human dignity and fundamental rights in South Africa and Ireland by Anne Hughes 2014 ISBN: 978-1-920538-21-7 Pages: 603 Print version: Available Electronic version: Free PDF available